Magnetic targeting combined with active targeting of dual-ligand iron oxide nanoprobes to promote the penetration depth in tumors for effective magnetic resonance imaging and hyperthermia. (15th September 2019) - Chen, Ling; Wu, Yang; Wu, Haoan; Li, Jianzhong; Xie, Jun; Zang, Fengchao; Ma, Ming; Gu, Ning; Zhang, Yu
Graphical abstract: Abstract: The combination of multi-targeting magnetic nanoprobes and multi-targeting strategies has potential to facilitate magnetic resonance imaging (MRI) and magnetic induction hyperthermia of the tumor. Although the thermo-agents based on magnetic iron oxide nanoparticles (MION) have been successfully used in the form of intratumoral injection in clinical cure of glioblastoma, the tumor-targeted thermotherapy by intravenous administration remains challenging. Herein, we constructed a c(RGDyK)- and d -glucosamine-grafted bispecific molecular nanoprobe (Fe3 O4 @RGD@GLU) with a magnetic iron oxide core of size 22.17 nm and a biocompatible shell of DSPE-PEG2000, which can specially target the tumor vessel and cancer cells. The selection of c(RGDyK) could make the nanoprobe enter the neovascularization endotheliocyte through αv β3 -mediated endocytosis, which drastically reduced the dependence on the enhanced permeability and retention (EPR) effect in tumor. This dual-ligand nanoprobe exhibited strong magnetic properties and favorable biocompatibility. In vitro studies confirmed the anti-phagocytosis ability against macrophages and the specific targeting capability of Fe3 O4 @RGD@GLU. Then, the imaging effect and anti-tumor efficacy were compared using different targeting strategies with untargeted nanoprobes, dual-targeted nanoprobes, and magnetic targeting combined with dual-targeted nanoprobes. Moreover, the combination strategy of magnetic targeting and active targeting promoted the penetration depth of nanoprobes in addition to the increased accumulation in tumor tissue. Thus, the dual-targeted magnetic nanoprobe together with the combined targeting strategy could be a promising method in tumor imaging and hyperthermia through in vivo delivery of theranostic agents. Statement of Significance: Magnetic induction hyperthermia based on iron oxide nanoparticles has been used in clinic for adjuvant treatment of recurrent glioblastoma. Nonetheless, this application is limited to intratumoral injection, and tumor-targeted hyperthermia by intravenous injection remains challenging. In this study, we developed a multi-targeted strategy by combining magnetic targeting with active targeting of dual-ligand magnetic nanoprobes. This combination mode acquired optimum contrast imaging effect through MRI and tumor-suppressive effect through hyperthermia under an alternating current magnetic field. The design of the nanoprobe was suitable for targeting most tumor lesions, which enabled it to be an effective theranostic agent with extensive uses. This study showed significant enhancement of the penetration depth and accumulation of nanoprobes in the tumor tissue for efficient imaging and hyperthermia.